The relationship determination between menarche and the peak of skeletal maturation using hand wrist and cervical vertebrae index - Endah Mardiati; Soemantry ES; Haroen ER; Thahar B; Sutrisna B (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: Menarche and skeletal maturation indices are physiological maturation indicators that can be used to establish the maturation stage of individual patient in orthodontic treatment, especially in orthodontic growth modification and orthognatic surgery. Purpose: The purpose of this study was to determine the relationship between menarche and the peak of skeletal maturation using hand-wrist and cervical vertebrae indexes. Methods: This was an observational diagnostic research with 220 female of Deutero-Malay Indonesian subjects aged 8-17 years from Dental Hospital Faculty of Dentistry Universitas Padjadjaran, and some privates orthodontic practice in Bandung. All subjects had hand-wrist radiograph and lateral cephalogram. Menarche data were collected through interview with the subjects and their parents. There were 89 subjects who already had menarche but only 84 of them remembered the month and year of their menarche. The stage of hand-wrist skeletal maturation was analyzed using Fishman method and cervical vertebrae maturation was analyzed using Baccetty et.al., method. Results: The result indicates that the menarche age of Indonesian DeuteroMalay subject were 12.47 ± 0.73 year. The youngest age of were 10.92 ± 0.0 year and the oldest were 13.83 ± 0.23 year. Conclusion: Menarche could be used as an indicator that the pubertal growth peak has been exceeded and to predict the end of the pubertal growth. This study showed that 0.49 years after MP3cap stage of hand-wrist skeletal maturation index and 0.69 years after CVMS2 stage of cervical vertebrae skeletal maturation index, the subject of Indonesian Deutero-Malay will have their menarche. Latar belakang: Menarke dan indeks maturasi skeletal merupakan indikator maturasi fisologis yang dapat digunakan untuk menentukan tahap maturasi pasien pada perawatan ortodonti modifikasi pertumbuhan dan bedah ortognati. Tujuan: Tujuan penelitian ini adalah menentukan hubungan antara menarke dengan puncak pertumbuhan skeletal dengan menggunakan indikator maturasi handwrist dan vertebra servikal. Metode: Penelitian ini merupakan penelitian diagnostik obeservasional dengan 220 subjek perempuan umur 8-17 tahun yang datang ke Rumah Sakit Gigi dan Mulut Universitas Padjadjaran Bandung. Seluruh subjek penelitian mempunyai foto rontgen hand-wrist dan sefalogram lateral. Data menarke diperoleh melalui wawancara kepada pasien dan orang tuanya. Subjek yang telah mengalami menarke sebanyak 89 orang tetapi hanya 84 subjek yang ingat dengan tepat bulan dan tahunnya. Tahap maturasi hand-wrist dianalisis dengan menggunakan metode Fishman dan tahap maturasi vertebra servikal ditentukan dengan menggunakan metode Baccety dkk. Hasil: Hasil penelitian menunjukkan bahwa rata-rata umur menarke terjadi pada umur 12.47 ± 0,73 tahun, dengan umur termuda pada10,92 ± 0,0 tahun dan tertua pada umur13,83 ± 0,23 tahun. Simpulan: Menarke dapat digunakan sebagai indikator untuk menentukan bahwa puncak pubertas telah terlampaui dan untuk memprediksi akhir pertumbuhan pubertal. Studi ini menunjukkan bahwa 0,49 tahun setelah MP3cap stage dari maturasi skeletal pergelangan tangan dan 0,69 tahun setelah CVMS2 maturasi skeletal vertebra leher anak perempuan Indonesia deutero melayu akan memasuki masa haid.